Punic people were genetically diverse with almost no Levantine ancestors - Ringbauer, Harald; Salman-Minkov, Ayelet; Regev, Dalit; Olalde, Iñigo; Peled, Tomer; Sineo, Luca; Falsone, Gioacchino; van Dommelen, Peter; Mittnik, Alissa; Lazaridis, Iosif; Pettener, Davide; Bofill, Maria; et al. (Springer, 2025)
The maritime Phoenician civilization from the Levant transformed the entire Mediterranean during the first millennium bce1,2,3. However, the extent of human movement between the Levantine Phoenician homeland and Phoenician–Punic settlements in the central and western Mediterranean has been unclear in the absence of comprehensive ancient DNA studies. Here, we generated genome-wide data for 210 individuals, including 196 from 14 sites traditionally identified as Phoenician and Punic in the Levant, North Africa, Iberia, Sicily, Sardinia and Ibiza, and an early Iron Age individual from Algeria. Levantine Phoenicians made little genetic contribution to Punic settlements in the central and western Mediterranean between the sixth and second centuries bce, despite abundant archaeological evidence of cultural, historical, linguistic and religious links4. Instead, these inheritors of Levantine Phoenician culture derived most of their ancestry from a genetic profile similar to that of Sicily and the Aegean. Much of the remaining ancestry originated from North Africa, reflecting the growing influence of Carthage5. However, this was a minority contributor of ancestry in all of the sampled sites, including in Carthage itself. Different Punic sites across the central and western Mediterranean show similar patterns of high genetic diversity. We also detect genetic relationships across the Mediterranean, reflecting shared demographic processes that shaped the Punic world.
Please see the document for a full list of funding organisations.
Keywords: General Science & Technology